Eating Competence in First-Generation Students at a Northeastern, Public University. (7th June 2021) - Jones, Erica; Morrell, Jesse Stabile
Abstract: Objectives: To assess differences in eating competence (EC) between first-generation students (FG) and students with 1 + parents who graduated from college (non-FG), in students 18–24 years old, at a large, northeastern, public university. Methods: Data were collected between 2015–2020 from the College Health and Nutrition Assessment Survey, an ongoing, cross-sectional study at a northeastern university. Participants ( n  = 1974) completed the Eating Competence Satter Inventory (ecSI 2.0 TM ) and self-reported education status of both parents through an online survey (Qualtrics) during the 3 rd or 4 th week of classes. ecSI scores range from 0–48; eating competence was defined as ≥32. Subgroups within the ecSI include Eating Attitudes, Food Acceptance, Food Regulation and Contextual Skills. FG was defined if both parents did not obtain a college degree. ANCOVA evaluated differences between mean ecSI scores of FG vs. non-FG ( n  = 1478); age, gender, race, Pell Grant status, dining hall usage, athlete status, and available kitchen served as covariates. Results: In this sample, 64.9% of participants were female students, 25.2% were FG, and had a mean age of 19.0 ± 0.02 years. FG students ( n  = 496) had modestly lower mean ecSI scores than non-FG students (32.9 ± 0.4 vs. 34.0 ± 0.3, P  = 0.03. Subscale scores for Food Acceptance (0–9), Food Regulation (0–9) and Contextual Skills (0–12) were lower in FG students compared to non-FG students (5.1 ± 0.1 vs. 5.4 ± 0.7, P  = 0.03, 6.4 ± 0.1 vs. 6.6 ± 0.1, P  = 0.05, and 10.4 ± 0.1 vs. 10.9 ± 0.1, P  = 0.003 respectively). Conclusions: Results suggest FG students have lower EC scores than their non-FG counterparts; subscales suggest where FG students may need more support to achieve more favorable weight and health outcomes. More research in diverse communities of college students will help address the needs of FG students and strengthen outcomes for campus communities. Funding Sources: New Hampshire Agriculture Experiment Stations and the USDA National Institute of Food and Agriculture Hatch Project.